Fitogeografska delitev Slovenije in leksična raznolikost slovenskih narečij - Zupančič, Mitja (Traditiones (Ljubljana), 1999)
The study to present the similarity between the distribution of phytogeographical areas and lexemes, as the words for forest, corncob, Lady Day, and Palm Sunday bundle according to the SLA material), and lath (to lay tile), carpenter's hatchet, place for hay in barn, place for straw in barn, and barn (according to the carpenter's terminology material). Maps clearly shaw the accordance, more or less satisfactory, with the areas
Keywords: fitogeografske karte; dialektološke karte; dialectology; dialektologija; narečja; dialect; slovenska narečja; Slovene dialects; fitogeografija; Slovenia; Slovenija